Pendidikan Moral Lawrence Kohlberg dan Pendidikan Karakter Thomas Lickona dalam Bingkai Pendidikan Nilai - Fadli, Muhammad Ulfi (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
This article aims to find out how value education is seen from the teroi moral education of Lawrence Kohlberg and Thomas Lickona's theory of character education. The method used in this study uses literature analysis of data taken from books, journals and other literature relevant to Lawrence Kohlberg's moral education and Thomas Lickona's character education in the frame of value education. The results of the study show that morals and character are very important in value education. The moral development of Lawrence Kohberg has three stages, namely the pre-conventional level consisting of the punishment and obedience orientation stage and the instrumental-relativist orientation or hedonistic orientation stage, the two stages at the conventional level consisting of the interpersonal concordance stage, the law and order orientation stage, and the stage for the level of post-conventional which consists of the social-contract stage, legalistic orientation and the orientation of universal ethical principles. While Thomas Lickona has an approach that is used as a learning objective, including the value planting approach, the cognitive development approach, the value analysis approach, and the value clarification approach.